(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Among the main problems are depletion of the ozone layer, global warming, atmospheric air pollution, pollution of the world’s oceans and reduction of biological diversity living on earth. The problem of atmospheric pollution can also be included among the most acute environmental problems of concern to the world community.